Religious Identity Politics on Social Media in Indonesia: A Discursive Analysis on Islamic Civil Societies - ARI GANJAR HERDIANSAH; LUTHFI HAMZAH HUSIN; HENDRA - (Universitas Muhammadiyah Yogyakarta, 2018)
Since 2014, religious sentiment in Indonesian social media has been increasingly overwhelming. The strong religiosity of society leads to religious packaging to help convey any political articulation in social media especially conducted by the Islamic civil societies. This article examines the political articulation uttered by Muhammadiyah, NU, and Muslim Cyber Army (MCA) as a representation of the democratization of Islamic civil society in responding to the contemporary political situation. Using the discursive analysis constructed by Laclau, this paper attempts to explain how Islamic organizations and groups build discourse and maintain its influence in social media as an alternative tone of political articulation. The results of this study indicate that social media has become a contested space of Islamic organizations and group to show their political position upon the government. The more an organization is close to the power the more it tends to reveal articulations that are in line with the government interest. Meanwhile, the opposing and incapable groups securing the social media a tool to delegitimized the authorities. The use of social media as political articulation has maintained democratization among Islamic civil society but within the limits of democratic values applied. Social media can also be used to strengthen the discourse of religious politicization that has the potential to contradict democratization itself.